Desenvolvimento e aplicação do ELISA indireto com proteína recombinante de nucleocapsídeo de coronavírus felino (FCoV) para quantificação de anticorpos em soros de gatos naturalmente infectados - Almeida, Ariani Cristina da Silva [UNESP] (2013)
The Feline Coronavírus (FCoV) is a member of the Nidovirales order, Coronaviridae family, Alphacoronavírus genus, which is responsible for causing Feline Infectious Peritonitis (FIP). Among the serological tests used in the disease diagnosis, ELISA is the most sensitive and recommended assay. FCoV has characteristics that difficult their cell culture growing, requiring the use of recombinant antigens in the ELISA. The FCoV nucleocapsid protein (N) is conserved, highly immunogenic and is the most protein produced during viral infection, being a great recombinant antigen in serological tests. The aim of this study was to standardize and apply the indirect ELISA using recombinant N protein to detect anti-FCoV antibodies in sera from naturally infected cats. A kidney fragment of died feline FIP positive was used for extraction of viral RNA, amplification by RT-PCR and sequencing of the protein N. The N protein sequence was synthesized with optimized codons for expression in Escherichia coli and inserted into pGS21a plasmid. The protein was produced, purified and the Western blotting was performed with sera from naturally infected cat to confirm the reactivity of the protein. To indirect ELISA standardization, the antigen concentration, serum dilution and the blocking reagent were determined. Three hundred eighty-two cat’s sera were tested. The obtained results showed that the protein presented good reactivity in indirect ELISA. The A450 differences from 0.1 to 1.8 showed the quantitative feature of the assay. The standardized indirect ELISA for detection of anti-FCoV using recombinant N protein is efficient and can be applied in field samples